Carbon pricing : early experience and future prospects - Quiggin, John.; Adamson, David; Quiggin, Daniel; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2014)
In 2012, Australia took the major step of introducing a carbon price, involving the creation of a system of emissions permits initially issued at a fixed price. Carbon Pricing brings together experts instrumental in the development, and operation, of Australia's carbon policy who have played a significant role in the broader debate over climate change policy. Together they have achieved an in-depth analysis of Australia's policy stance on pricing carbon and its implications for the wider economy. While the future of carbon pricing is itself unclear in Australia, the experiences, insights and conclusions outlined herein will prove invaluable to a global audience. The assessment of the initial operation of the carbon price provides a wide range of insights into the problems of mitigating climate change, and the prospects for the future. The critical analysis will provide a valuable resource to inform wider international debates concerning alternative mechanisms for internalising the carbon externality, tax reform, climate scepticism and carbon farming initiatives. With its interdisciplinary approach, Carbon Pricing, will appeal to scholars and researchers of economics in general and climate change, natural resources and energy policy in particular. Those organisations and policymakers involved in similar experiments and processes in other countries will find the experiences and analysis invaluable.
1. The carbon tax : early experience and future prospects / Ross Garnaut -- 2. Carbon pricing in Australia : an early view from the inside / Daniel Besley ... [et al.] -- 3. How has the carbon tax affected the public'debate' on climate change? / John Cook -- 4. The carbon tax and tax reform debate / John Freebairn -- 5. How I learned to stop worrying and love the RET / John Quiggin -- 6. The impact of carbon prices on Australia's national energy market / Phillip Wild, William Paul Bell and John Foster -- 7. Modeling the impact of the Australian greenhouse emissions trading scheme on farm and fishery businesses / Mick Keogh -- 8. Science, transaction costs and carbon markets / Michael Battaglia and Rohan Nelson -- 9. Agricultural adaptation : observations and insights / Thilak Mallawaarachchi and Michael Harris -- 10. Climate change and the precautionary principle / Simon Grant and John Quiggin.
Includes index.
Keywords: Carbon offsetting; Emissions trading